Experiments in mathematics - Borwein, Jonathan; Bailey, David; Girgensohn, Roland ([S.l.] : A K Peters, 2006)
This experiments in mathematics CD contains the full text of both text book mathematics by experimen: plausible reasoning in the 21st century and experimentation in mathematics: computational paths to discovery in electronic searchable form
System requirement: Adobe Acrobat Reader 8.1.0
Keywords: Mathematics -- Data processing; Mathematics -- Experiments